Immobilized Acylase PvdQ Reduces Pseudomonas aeruginosa Biofilm Formation on PDMS Silicone - Vogel, Jan; Wakker-Havinga, Marijke; Setroikromo, Rita; Quax, Wim J. (Frontiers in Chemistry, 2020)
The bacterial biofilm plays a key role in nosocomial infections, especially those related to medical devices in sustained contact with patients. The active dispersion of bacterial cells out of biofilms act as a reservoir for infectious diseases. The formation of such biofilms is a highly complex process, which is coordinated by many regulatory mechanisms of the pathogen including quorum sensing (QS). Preventing the development of biofilms is considered a promising approach to prevent the development of hard to treat infections. Quorum quenching is the concept of interfering with the QS system of bacteria. PvdQ is an Ntn-hydrolase that is able to cleave irreversibly the amide bond of long chain N-acyl homoserine lactones (AHL) rendering them inactive. Long chain AHLs are the main signaling molecule in the QS system of the gram-negative pathogen Pseudomonas aeruginosa, which is known for surface-associated biofilms on indwelling catheters and is also the cause of catheter-associated urinary tract infections. In this study, we immobilized the acylase PvdQ on PDMS silicone, creating a surface with quorum quenching (QQ) properties. The goal is to control infections by minimizing the colonization of indwelling medical devices such as urinary catheters or intravascular catheters. The enzyme activity was confirmed by testing the degradation of the main auto inducer that mediates QS in P. aeruginosa. The immobilized enzyme caused a significant reduction in P. aeruginosa PA01 biofilm formation on a silicone surface.